2019
DOI: 10.1111/cup.13607
|View full text |Cite
|
Sign up to set email alerts
|

Basaloid tumors arising from seborrheic keratosis: Malignant basal cell carcinoma or benign basaloid follicular hamartomatous proliferation?

Abstract: Background: Basaloid tumors arising from seborrheic keratosis (SK) that resembled basal cell carcinoma (BCC) were infrequently observed in our patients. They also exhibited morphologic features similar to those of trichoblastoma or basaloid follicular hamartoma. Methods:We retrospectively collected cases of SK with basaloid tumors from 2001 to 2017. Ten cases of BCC, five of nevus sebaceus with trichoblastoma, five of trichoblastoma, and five of trichoepithelioma were included as controls. Tumorassociated anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Kramer et al also found no correlation between the proliferative index and the aggressive patterns of BCC [ 39 ]. Other studies reported that Ki67 expression was positive in all of the BCC subtypes but varied in intensity between recurrent BCCs and non-recurrent ones, with a higher expression of Ki67 in the recurrent cases [ 40 , 41 ]. Horlock et al observed that the morpheaform, infiltrating and superficial subtypes of BCC had the most intense Ki67 reactivity and highlighted the association between high levels of proliferation and BCC subtypes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kramer et al also found no correlation between the proliferative index and the aggressive patterns of BCC [ 39 ]. Other studies reported that Ki67 expression was positive in all of the BCC subtypes but varied in intensity between recurrent BCCs and non-recurrent ones, with a higher expression of Ki67 in the recurrent cases [ 40 , 41 ]. Horlock et al observed that the morpheaform, infiltrating and superficial subtypes of BCC had the most intense Ki67 reactivity and highlighted the association between high levels of proliferation and BCC subtypes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that Ki67 expression was positive in all of the BCC subtypes but varied in intensity between recurrent BCCs and non-recurrent ones, with a higher expression of Ki67 in the recurrent cases [40,41].…”
Section: Figure 5 -Cd44 Immunoexpression In: (A) Control; (B) Superfi...mentioning
confidence: 99%
“…Combined cases of seborrheic keratosis and basal cell carcinoma have also been reported in several articles. 12,15,16,28,[40][41][42][43][44][45][46][47][48][49] In such cases, the transition from seborrheic keratosis to basal cell carcinoma has not been clearly confirmed. Instead, nests of basal carcinoma are scattered throughout the seborrheic keratosis or collide with adjoining seborrheic keratosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although FMBFH generally presents at birth or in early childhood, milder variants may be recognized later in life [6,7]. Generalized forms of BFH are usually associated with systemic manifestations, which vary according to the subtype and can include cystic fibrosis, diffuse alopecia, and various autoimmune diseases (such as myasthenia gravis or systemic lupus erythematosus), [2,8,9]. Other systemic diseases, such as hypertension, diabetes mellitus, or breast cancer, have also been reported in these patients, although it is unclear if this association exceeds that found in the general population.…”
Section: Case Discussionmentioning
confidence: 99%
“…Vismodegib, an inhibitor of the hedgehog signaling pathway, might play a role in the treatment of severe disease in the future [12]. The prognosis is usually excellent, unless associated systemic disorders and/or BCC develop [8,9].…”
Section: A B Cmentioning
confidence: 99%